SYNTHESIS OF A CATION EXCHANGER FROM COMMERCIAL / RESIDUAL POLYSTYRENE - Cjuno H., J. Américo (2005)
Residual commercial polystyrene samples (PScr) have been undergone to thermal decomposition processes between 433 hand 673 K (160 at 400 °C). The analyses of the distilled have confirmed that PS has been transformed into styrene with a yield from 45 to 60%. The monomer obtained has been polymerized in suspension using benzoyl peroxide like initiator and divinylbenzene (DVB) in proportions of 2, 6 and 10%. The obtained microspheres of copolymer (PS-DVB) have been sulfonated. After characterization, the results showed that 6% of DVB, presents similar characteristic than the commercial strongly acid cationic exchange resin Sybron Chemicals Inc. Ionac ® C-249.